Analysis of the Effects of Environment on the Performance of Free Space Earth-to-Satellite Optical Link in Malaysia - Mohd Nor, Norhanis Aida; Islam, Md. Rafiqul; Al-Khateeb, Wajdi Fawzi Mohammed (2011)
Free Space Optics (FSO) is a promising optical technology that has a great chance to compliment the traditional wireless communications especially for applying this technology to satellite. It offers some inherent advantages compared to RF such as smaller telescopes, low power consumption, no frequency restrictions, no electromagnetic interference, and large increase in bandwidth. However, FSO is highly attenuated by weather because air is the medium of transmission channel. Moreover,recent studies mostly based on terrestrial link and focusing on temperate region which the attenuation is dominant by fog and snow. Therefore, this paper is aiming to provide FSO analysis of environmental effect for slant path that link from earth to Low Earth Orbit (LEO) satellite that occurs in tropical climate region where rain and haze are present throughout the year. The result of the analysis can provide more knowledge on the feasibility of performing FSO from earth-to-satellite under tropical region.